Composite negative electrode sheet, preparation method thereof and sodium ion battery
Patent Information
- Application Number
- CN202611411854.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-11
- Publication Date
- 2026-10-30
AI Technical Summary
由于单一孔隙率分布,钠离子倾向于在靠近隔膜一侧的负极表面优先沉积,导致该区域离子通量集中,易诱发钠枝晶生长;同时,集流体侧活性材料的荷电状态(SOC)低于隔膜侧,尤其在倍率充放电条件下,离子传输动力学受限,影响了电池容量的充分发挥
本申请提供一种复合负极片,通过采用包含第一硬碳材料的底层与包含第二硬碳材料的表层所构成的双层复合涂层结构,并利用两层硬碳材料在斜坡区/平台区容量比值(R值)上的差异,实现了电极功能梯度的精准构筑。具体而言,紧邻集流体的底层采用R值较低的第一硬碳材料,其平台区容量贡献大、克容量高,能够在集流体侧提供高容量的储钠能力,同时形成高电子导电的"快速通道",有利于电子的高效传导,兼顾了电极的能量密度与倍率性能;而位于表层的第二硬碳材料具有较高的R值,其斜坡区容量贡献大、钠离子扩散能垒低,且通过优化颗粒尺寸及匹配较高孔隙率,显著提升了极片表层的离子传输效率。由此,本申请实现了材料本征储钠特性与电极厚度方向上不同位置功能需求的合理匹配,避免了传统均匀涂层中离子通量集中于隔膜侧所导致的钠枝晶生长及集流体侧荷电状态偏低的问题。
Smart Images

Figure CN123017884A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of sodium-ion battery preparation technology, and in particular to a composite negative electrode sheet, its preparation method, and a sodium-ion battery. Background Technology
[0002] Sodium-ion batteries have broad application prospects in large-scale energy storage and low-speed electric vehicles due to the abundance and low cost of sodium resources. Hard carbon materials, as one of the anode materials for sodium-ion batteries, have attracted widespread attention in the field of high-power and long-life batteries because of their abundant sodium storage active sites, good rate performance, and cycle stability.
[0003] Typical sodium intercalation (charging) curves for hard carbon typically include a sloping ramp section in the high-voltage region and a plateau section in the low-voltage region (below approximately 0.1 V). The ramp capacity mainly originates from the adsorption behavior of sodium ions in the defects and open-pore structures on the hard carbon surface, a process with a low ion migration energy barrier; the plateau capacity corresponds to the intercalation process of sodium ions into the interlayer of graphite-like microcrystals, a process with a high diffusion energy barrier.
[0004] Currently, hard carbon anodes generally employ a single-layer uniform coating structure, which exhibits a uniform porosity along the electrode thickness direction. Due to this uniform porosity distribution, sodium ions tend to preferentially deposit on the anode surface near the separator, leading to concentrated ion flux in this region and easily inducing sodium dendrite growth. Simultaneously, the state of charge (SOC) of the active material on the current collector side is lower than that on the separator side. Especially under high-rate charge-discharge conditions, ion transport kinetics are limited, affecting the full utilization of battery capacity. Furthermore, if the hard carbon material near the separator side has a large plateau region capacity contribution (i.e., the pore-filling mechanism is dominant, and the reaction kinetics are slow), the electrolyte is prone to reduction and decomposition on its surface during long-term operation at low potentials, forming an unstable solid electrolyte interphase (SEI) film. Especially during high-current charge-discharge or later stages of cycling, sodium deposition is highly likely, severely restricting battery safety and lifespan. Summary of the Invention
[0005] The purpose of this application is to provide a composite negative electrode sheet, a method for preparing the same, and a sodium-ion battery to solve the above-mentioned problems.
[0006] To achieve the above objectives, this application adopts the following technical solution: A composite negative electrode includes a current collector and a composite coating disposed on at least one surface of the current collector; The composite coating includes a base layer and a surface layer, wherein the base layer is disposed between the current collector and the surface layer; the base layer comprises a first hard carbon material, and the surface layer comprises a second hard carbon material; Wherein, the ratio R1 of the capacity of the ramp region to the capacity of the plateau region in the charging curve of the first hard carbon material is less than the ratio R2 of the capacity of the ramp region to the capacity of the plateau region in the charging curve of the second hard carbon material.
[0007] Optionally, R1 ≤ 0.3.
[0008] Optionally, R2 satisfies 0.3 < R2 ≤ 1.8.
[0009] Optionally, the ramp region is the area in the charging curve where the voltage is higher than 0.1V; Optionally, the platform region is the area in the charging curve where the voltage is below 0.1V.
[0010] Optionally, the first hard carbon material and the second hard carbon material each independently include one or more of resin carbon, organic polymer carbon, and biomass carbon.
[0011] Optionally, the particle size of the first hard carbon material is 6-12 μm.
[0012] Optionally, the particle size of the second hard carbon material is 2-6 μm.
[0013] Optionally, the porosity of the bottom layer is 15-30%.
[0014] Optionally, the porosity of the surface layer is 20-55%.
[0015] This application also provides a method for preparing the composite negative electrode, comprising: A first slurry is prepared by mixing a first hard carbon material, a first conductive agent, a first binder, and a first solvent. A second slurry is prepared by mixing a second hard carbon material, a second conductive agent, a second binder, and a second solvent. The first slurry and the second slurry are placed on the surface of the current collector to form a composite wet film; after drying, rolling and slitting, the composite negative electrode sheet is obtained.
[0016] Optionally, a double-layer coating process is used to coat the first slurry and the second slurry on the surface of the current collector; The double-layer coating process includes a double-layer single-coating process or a double-layer stepped coating process.
[0017] Optionally, the double-layer coating process includes: The first slurry is coated on the surface of the current collector to form a bottom wet film. Before the bottom wet film is completely dry, the second slurry is coated on the bottom wet film to form a surface wet film.
[0018] Optionally, the first conductive agent and the second conductive agent each independently include one or more of carbon black, acetylene black, carbon fiber, graphene, or carbon nanotubes.
[0019] Optionally, the first adhesive and the second adhesive each independently include one or more of sodium carboxymethyl cellulose, polyacrylic acid, or styrene-butadiene rubber.
[0020] Optionally, the solid content of the first slurry is 15-50%.
[0021] Optionally, the solid content of the second slurry is 15-50%.
[0022] This application also provides a sodium-ion battery, including the composite negative electrode sheet.
[0023] Compared with the prior art, the beneficial effects of this application include: This application provides a composite negative electrode sheet, which employs a double-layer composite coating structure consisting of a bottom layer containing a first hard carbon material and a surface layer containing a second hard carbon material. By utilizing the difference in the capacity ratio (R-value) of the two hard carbon layers in the slope / plateau region, a precise functional gradient of the electrode is achieved. Specifically, the bottom layer adjacent to the current collector uses a first hard carbon material with a lower R-value. Its plateau region capacity contribution and specific capacity are high, providing high sodium storage capacity on the current collector side. Simultaneously, it forms a "fast channel" with high electronic conductivity, facilitating efficient electron conduction and balancing the electrode's energy density and rate performance. The second hard carbon material on the surface layer has a higher R-value, contributing significantly to the slope region capacity and exhibiting a low sodium ion diffusion barrier. Furthermore, by optimizing particle size and matching higher porosity, the ion transport efficiency of the electrode surface layer is significantly improved. Thus, this application achieves a reasonable match between the intrinsic sodium storage characteristics of the material and the functional requirements of different positions along the electrode thickness direction, avoiding the problems of sodium dendrite growth and low state of charge on the current collector side caused by the concentration of ion flux on the separator side in traditional uniform coatings.
[0024] The composite negative electrode preparation method provided in this application has a simple process flow, controllable equipment precision, and does not require major modifications to existing coating equipment. It has a good foundation for industrial promotion and adaptability to large-scale production.
[0025] The sodium-ion battery provided in this application, by employing the aforementioned composite negative electrode, achieves synergistic optimization of electronic conduction and ion transport within the cell. Specifically, the bottom layer near the current collector provides high-capacity sodium storage and excellent electronic conductivity pathways, effectively improving the cell's energy density; the surface layer near the separator provides high-rate ion transport channels, improving the insertion and extraction kinetics of sodium ions at the electrode / electrolyte interface. Through the complementary functions of the bottom and surface layers, the cell maintains good rate charge-discharge performance while achieving high energy density. Attached Figure Description
[0026] To more clearly illustrate the technical solutions of the embodiments of this application, the accompanying drawings used in the embodiments will be briefly described below. It should be understood that the following drawings only show some embodiments of this application and should not be regarded as a limitation on the scope of this application.
[0027] Figure 1 A schematic diagram of a gradient-distributed hard carbon anode structure; Figure 2 The coin cell intercalation curve for the combination of hard carbon and sodium sheet; Figure 3 The rate discharge capacity retention rates of Example 1, Comparative Example 1, and Comparative Example 5 are given.
[0028] The main icon numbers are shown below: 1- Negative electrode current collector; 2- Bottom layer hard carbon negative electrode; 3- Surface layer hard carbon negative electrode. Detailed Implementation
[0029] As used in this article: "Prepared from" is synonymous with "comprising". The terms "comprising", "including", "having", "containing", or any other variations thereof as used herein are intended to cover non-exclusive inclusion. For example, a composition, step, method, article, or apparatus that includes the listed elements is not necessarily limited to those elements, but may include other elements not expressly listed or elements inherent to such composition, step, method, article, or apparatus.
[0030] The conjunction "composed of..." excludes any unspecified elements, steps, or components. If used in a claim, this phrase makes the claim closed, excluding materials other than those described, except for associated conventional impurities. When the phrase "composed of..." appears in a clause of the body of a claim rather than immediately following it, it limits only the elements described in that clause; other elements are not excluded from the claim as a whole.
[0031] When a quantity, concentration, or other value or parameter is expressed as a range, a preferred range, or a range defined by a series of upper and lower preferred values, this should be understood as specifically disclosing all ranges formed by any pair of any upper or preferred value with any lower or preferred value, regardless of whether the range is disclosed individually. For example, when the range “1–5” is disclosed, the described range should be interpreted as including ranges “1–4”, “1–3”, “1–2”, “1–2 and 4–5”, “1–3 and 5”, etc. When numerical ranges are described herein, unless otherwise stated, the range is intended to include its endpoints and all integers and fractions within that range.
[0032] In these embodiments, unless otherwise specified, the portions and percentages are all by weight.
[0033] "Parts by mass" refers to the basic unit of measurement that expresses the mass ratio of multiple components. One part can represent any unit mass, such as 1g or 2.689g. If we say that component A has "a" parts by mass and component B has "b" parts by mass, it means the ratio of the mass of component A to the mass of component B is a:b. Alternatively, it can mean that the mass of component A is aK and the mass of component B is bK (where K is any number representing a multiplier). It is important to understand that, unlike parts by mass, the sum of the mass parts of all components is not limited to 100 parts.
[0034] "And / or" is used to indicate that one or both of the described situations may occur, for example, A and / or B includes (A and B) and (A or B).
[0035] To better explain the technical solution provided in this application, the technical solution provided in this application will be described in general before the specific implementation.
[0036] In a first aspect, this application provides a composite negative electrode sheet, including a current collector and a composite coating disposed on at least one surface of the current collector; The composite coating includes a base layer and a surface layer, wherein the base layer is disposed between the current collector and the surface layer; the base layer comprises a first hard carbon material, and the surface layer comprises a second hard carbon material; Wherein, the ratio R1 of the capacity of the ramp region to the capacity of the plateau region in the charging curve of the first hard carbon material is less than the ratio R2 of the capacity of the ramp region to the capacity of the plateau region in the charging curve of the second hard carbon material.
[0037] The above scheme achieves spatial decoupling and synergistic optimization of charge transport and ion transport by constructing gradient coatings with different electrochemical characteristics in the thickness direction, using the low R1 value material in the bottom layer to provide high plateau capacity to ensure energy density, and using the high R2 value material in the surface layer to provide excellent slope kinetic characteristics to promote rapid sodium ion transport.
[0038] In an optional implementation, R1 ≤ 0.3.
[0039] Optionally, R1 can be any value not greater than 0.3.
[0040] In an optional implementation, R2 satisfies 0.3 < R2 ≤ 1.8.
[0041] Optionally, R2 can be any value between 0.3 < R2 ≤ 1.8, or 0.4, 0.6, 0.8, 1.0, 1.2, 1.4, 1.6, 1.8.
[0042] This preferred scheme further limits the capacity ratio range of the bottom layer and the top layer materials, ensuring that the bottom layer has a sufficiently high plateau region capacity contribution to maintain the cell energy density, while the top layer has a moderate slope region capacity ratio to balance dynamic performance and volumetric energy density, avoiding a decrease in overall compaction density due to an excessively high R2 value in the top layer.
[0043] In an alternative implementation, the ramp region is the area in the charging curve where the voltage is higher than 0.1V.
[0044] In an alternative implementation, the plateau region is the area in the charging curve where the voltage is below 0.1V.
[0045] In one optional embodiment, the first hard carbon material and the second hard carbon material each independently include one or more of resin carbon, organic polymer carbon, and biomass carbon.
[0046] In one optional embodiment, the particle size of the first hard carbon material is 6-12 μm.
[0047] Optionally, the particle size of the first hard carbon material can be 6μm, 8μm, 10μm, 12μm, or any value between 6 and 12μm.
[0048] In one optional embodiment, the particle size of the second hard carbon material is 2-6 μm.
[0049] Optionally, the particle size of the second hard carbon material can be 2 μm, 4 μm, 6 μm, or any value between 2 and 6 μm.
[0050] In one alternative implementation, the porosity of the substrate is 15-30%.
[0051] Optionally, the porosity of the bottom layer can be 15%, 20%, 25%, 30%, or any value between 15% and 30%.
[0052] In one alternative embodiment, the porosity of the surface layer is 20-55%.
[0053] Optionally, the porosity of the surface layer can be 20%, 25%, 30%, 35%, 40%, 45%, 50%, or any value between 20% and 55%.
[0054] This preferred design constructs a physical gradient structure with decreasing particle size and increasing porosity from the current collector side to the diaphragm side through synergistic control of material type, particle size distribution, and porosity. The large-particle-size bottom layer is beneficial for improving compaction density and electronic conductivity, while the small-particle-size, high-porosity surface layer shortens the ion diffusion path and increases the electrolyte wetting area, further enhancing the practical effect of the gradient functional design.
[0055] Secondly, this application also provides a method for preparing the composite negative electrode, comprising: A first slurry is prepared by mixing a first hard carbon material, a first conductive agent, a first binder, and a first solvent. A second slurry is prepared by mixing a second hard carbon material, a second conductive agent, a second binder, and a second solvent. The first slurry and the second slurry are placed on the surface of the current collector to form a composite wet film; after drying, rolling and slitting, the composite negative electrode sheet is obtained.
[0056] The above preparation method achieves precise construction of gradient structures by preparing slurries with different active substances and performing composite coating. It has strong process compatibility and is easy to scale up for production.
[0057] In an optional embodiment, a two-layer coating process is used to coat the first slurry and the second slurry onto the surface of the current collector; The double-layer coating process includes a double-layer single-coating process or a double-layer stepped coating process.
[0058] This implementation utilizes a double-layer coating equipment to achieve continuous or stepwise coating of two layers of slurry, improving production efficiency and coating thickness accuracy. The double-layer single coating can also utilize the mutual solubility effect at the wet film interface to enhance interlayer bonding.
[0059] In one optional implementation, the double-layer coating process includes: The first slurry is coated on the surface of the current collector to form a bottom wet film. Before the bottom wet film is completely dry, the second slurry is coated on the bottom wet film to form a surface wet film.
[0060] The preferred solution uses a wet-on-wet coating method, which allows the two slurries to penetrate and fuse to a certain extent at the interface, forming a gradient transition interface. This effectively avoids the interlayer delamination problem that may occur in dry lamination and improves the mechanical integrity and ion translayer transport capability of the electrode.
[0061] In one alternative embodiment, the first conductive agent and the second conductive agent each independently include one or more of carbon black, acetylene black, carbon fiber, graphene, or carbon nanotubes.
[0062] In an alternative embodiment, the first adhesive and the second adhesive each independently comprise one or more of sodium carboxymethyl cellulose, polyacrylic acid, or styrene-butadiene rubber.
[0063] This implementation provides a specific range of conductive agents and binders to ensure the formation of a stable electronic conductive network and mechanical bonding strength within each coating, while also taking into account the rheological properties of the slurry and the flexibility of the electrode.
[0064] In one optional embodiment, the solid content of the first slurry is 15-50%.
[0065] Optionally, the solid content of the first slurry can be 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, or any value between 15% and 50%.
[0066] In one optional embodiment, the solid content of the second slurry is 15-50%.
[0067] Optionally, the solid content of the second slurry can be 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, or any value between 15% and 50%.
[0068] This preferred scheme limits the solid content window of the slurry, ensuring both uniform slurry dispersion and coating stability while balancing drying efficiency and coating density, which is beneficial for obtaining a gradient structure with porosity that meets design requirements.
[0069] This application also provides a sodium-ion battery, including the composite negative electrode sheet.
[0070] The implementation schemes of this application will be described in detail below with reference to specific embodiments. However, those skilled in the art will understand that the following embodiments are only for illustrating this application and should not be regarded as limiting the scope of this application. Unless otherwise specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall apply. Reagents or instruments used without specified manufacturers are all conventional products that can be purchased commercially.
[0071] Example 1 This embodiment provides a composite negative electrode sheet: A schematic diagram of a gradient-distributed hard carbon anode structure is shown below. Figure 1As shown, the composite negative electrode includes a current collector and a composite coating disposed on both sides of the current collector 1. The composite coating includes a bottom hard carbon negative electrode 2 and a top hard carbon negative electrode 3, with the bottom hard carbon negative electrode 2 disposed between the current collector 1 and the top hard carbon negative electrode 3. The bottom hard carbon negative electrode 2 contains a first hard carbon material, and the top hard carbon negative electrode 3 contains a second hard carbon material. The ratio R1 of the ramp region capacity to the plateau region capacity of the first hard carbon material in the charging curve is less than the ratio R2 of the ramp region capacity to the plateau region capacity of the second hard carbon material in the charging curve.
[0072] In this embodiment, the R1 of the first hard carbon material (biochar, made from coconut shells, purchased from Shenzhen BTR) is 0.28, and the R2 of the second hard carbon material (biochar, made from coconut shells, purchased from Shenzhen BTR) is 0.59. The particle size Dv50 of the first hard carbon material is 8.2 μm, and the particle size Dv50 of the second hard carbon material is 4.6 μm. The porosity of the bottom layer is 21%, and the porosity of the surface layer is 30%. The coating thickness of the bottom layer is 60 μm, and the coating thickness of the surface layer is 20 μm.
[0073] This embodiment also provides a method for preparing the composite negative electrode, the specific steps of which are as follows: Preparation of the first slurry: Using a dry homogenization method, 94.5% by weight of phenolic resin-based hard carbon anode (model BSHC-1, purchased from Shenzhen BTR), 0.5% by weight of CMC, and 2% by weight of conductive carbon black were added to a mixing tank for dry powder mixing. Then, 1.8% by weight of PAA adhesive (binder, purchased from Puyuan Materials) and an appropriate amount of deionized water were added to make the slurry into a dough-like state and kneaded for 60 minutes. After kneading, deionized water was added to adjust the viscosity to 1800 mPa·s and the fineness to no more than 40 μm. Finally, 1.2% of SBR adhesive was added and evenly dispersed to obtain the first slurry.
[0074] Preparation of the second slurry: A dry homogenization method was used. 94.5% by weight of phenolic resin-based hard carbon anode (model BSHC-1, purchased from Shenzhen BTR), 0.5% by weight of CMC (sodium carboxymethyl cellulose, NE760TH, purchased from Chongqing Shuoyingfeng New Energy Technology Co., Ltd.), and 2% by weight of conductive carbon black were added to a mixing tank for dry powder mixing. Then, 1.8% by weight of PAA adhesive (1205, purchased from Hubei Huitian New Materials Co., Ltd.) and an appropriate amount of deionized water were added to make the slurry into a dough-like state and kneaded for 60 minutes. After kneading, deionized water was added to adjust the viscosity to 1920 mPa·s and the fineness to no more than 40 μm. Finally, 1.2% by weight of SBR adhesive (styrene-butadiene rubber, S029, purchased from Xinxiang Jinbang Power Technology Co., Ltd.) was added and uniformly dispersed to obtain the second slurry.
[0075] A dual-layer coating method with dual die heads is used to apply the first and second slurries to the surface of the current collector 1 of the negative electrode sheet, forming a composite wet film. Specifically, the first slurry is coated on the surface of the current collector aluminum foil to form a bottom wet film. While the bottom wet film is not completely dry, the second slurry is coated on the bottom wet film to form a surface wet film, thus forming the bottom hard carbon negative electrode 2 and the surface hard carbon negative electrode 3. After coating one side of the current collector, the other side is coated in the same way, with a coating density of 110 g / m³ on one side. 2 .
[0076] This embodiment also provides a sodium-ion battery: This includes the aforementioned composite negative electrode. Details are as follows: Electrolyte: Ethylene carbonate (EC): Propylene carbonate (PC): Diethyl carbonate (DEC): Ethylene glycol dimethyl ether (DME): Dioxolane (DOL): Sodium hexafluorophosphate (NaPF6): Fluorinated ethylene carbonate (FEC): Vinyl carbonate (VC): Ethyl sulfate (DTD): Sodium difluorooxalate borate (NaDFOB): 1,3-propane sulpholactone (PST) = 20%: 20%: 19%: 10%: 10%: 14%: 3.5%: 1%: 0.5%: 0.5%: 1.5%.
[0077] The membrane can be a polymer membrane, a ceramic membrane, or a polymer / ceramic composite membrane. Polymer membranes include single-layer polymer membranes and multi-layer polymer membranes. Single-layer polymer membranes include polyethylene (PE) membranes and polypropylene (PP) membranes.
[0078] Sodium-ion batteries: A sodium-ion battery includes a cell and an electrolyte. The cell includes a positive electrode, a composite negative electrode, and a separator. The cell is manufactured by stacking the positive electrode, negative electrode, and separator according to design requirements (e.g., Z-shaped stacking or wound stacking). Therefore, this application also provides a sodium-ion battery. In an exemplary embodiment, the sodium-ion battery has an initial charge capacity >1330mAh, an initial discharge capacity >1190mAh, and is tested at 25°C according to a charge-discharge cycle of 1.5-4.0V and 0.5C / 1C.
[0079] After obtaining the battery cell, it is encapsulated in a casing. The process involves drying to remove moisture, injecting electrolyte, encapsulation, settling, formation, and high-temperature aging to produce a sodium-ion battery. The form of the sodium-ion battery in this application is not particularly limited; it can be a button-type sodium-ion battery, a cylindrical sodium-ion battery, a pouch sodium-ion battery, or an aluminum-cased sodium-ion battery.
[0080] The performance of the sodium-ion battery provided in this embodiment was tested, and the results are as follows: the cell energy density is 132.0Wh / Kg, and the capacity retention rate after 300 cycles at 45℃ is 94%.
[0081] Example 2 Compared with Example 1, the difference is that the particle size Dv50 of the second hard carbon material is 2.0 μm, and the porosity of the surface layer is 33%. All other parameters and preparation methods are the same as in Example 1.
[0082] The performance of the sodium-ion battery provided in this embodiment was tested, and the results are as follows: the cell energy density is 131.5Wh / Kg, and the capacity retention rate after 300 cycles at 45℃ is 92.3%.
[0083] Example 3 Compared with Example 1, the difference is that the thickness of the bottom coating is 70 μm and the thickness of the top coating is 10 μm. All other parameters and preparation methods are the same as in Example 1.
[0084] The performance of the sodium-ion battery provided in this embodiment was tested, and the results are as follows: the cell energy density is 131.2Wh / Kg, and the capacity retention rate after 300 cycles at 45℃ is 90.4%.
[0085] Example 4 Compared with Example 1, the difference is that the particle size Dv50 of the first hard carbon material is 6 μm. All other parameters and preparation methods are the same as in Example 1.
[0086] The performance of the sodium-ion battery provided in this embodiment was tested, and the results are as follows: the cell energy density is 133.6Wh / Kg, and the capacity retention rate after 300 cycles at 45℃ is 92.1%.
[0087] Example 5 The difference compared to Example 1 is that the R² of the second hard carbon material is 0.45. All other parameters and preparation methods are the same as in Example 1.
[0088] The performance of the sodium-ion battery provided in this embodiment was tested, and the results are as follows: the cell energy density is 129.3Wh / Kg, and the capacity retention rate after 300 cycles at 45℃ is 93.5%.
[0089] Example 6 The difference compared to Example 1 is that the R² of the second hard carbon material is 0.7. All other parameters and preparation methods are the same as in Example 1.
[0090] The performance of the sodium-ion battery provided in this embodiment was tested, and the results are as follows: the cell energy density is 133.8Wh / Kg, and the capacity retention rate after 300 cycles at 45℃ is 94.3%.
[0091] Comparative Example 1 Compared to Example 1, the difference is that the composite coating does not contain a surface layer, i.e., the surface layer thickness is 0, and it only contains the bottom layer (thickness is 80 μm). R2 of the second hard carbon material is absent ( / ). All other parameters and preparation methods are the same as in Example 1.
[0092] The performance of the sodium-ion battery provided in this comparative example was tested, and the results are as follows: the cell energy density is 120.9Wh / Kg, and the capacity retention rate after 300 cycles at 45℃ is 82.6%.
[0093] Comparative Example 2 Compared to Example 1, the difference is that the composite coating does not contain an underlayer, i.e., the underlayer thickness is 0, and it only contains a surface layer (thickness of 80 μm). R1 of the first hard carbon material is absent ( / ). All other parameters and preparation methods are the same as in Example 1.
[0094] The performance of the sodium-ion battery provided in this comparative example was tested, and the results are as follows: the cell energy density is 127.9Wh / Kg, and the capacity retention rate after 300 cycles at 45℃ is 91.2%.
[0095] Comparative Example 3 Compared with Example 1, the differences are as follows: the R1 of the first hard carbon material is 0.35, the particle size Dv50 of the first hard carbon material is 4.6 μm, and the particle size Dv50 of the second hard carbon material is 8.2 μm; the thickness of the bottom coating is 20 μm, and the thickness of the top coating is 60 μm; the porosity of the bottom layer is 30%, and the porosity of the top layer is 21%. All other parameters and preparation methods are the same as in Example 1.
[0096] The performance of the sodium-ion battery provided in this comparative example was tested, and the results are as follows: the cell energy density is 122.3Wh / Kg, and the capacity retention rate after 300 cycles at 45℃ is 92.9%.
[0097] Comparative Example 4 The difference between Example 1 and Example 2 is that the particle size Dv50 of the second hard carbon material is 8.6 μm. All other parameters and preparation methods are the same as in Example 1.
[0098] The performance of the sodium-ion battery provided in this comparative example was tested, and the results are as follows: the cell energy density is 123.1Wh / Kg, and the capacity retention rate after 300 cycles at 45℃ is 93.3%.
[0099] Comparative Example 5 Compared with Example 1, the difference is that the R2 of the second hard carbon material is 0.25. All other parameters and preparation methods are the same as in Example 1.
[0100] The performance of the sodium-ion battery provided in this comparative example was tested, and the results are as follows: the cell energy density is 125.6Wh / Kg, and the capacity retention rate after 300 cycles at 45℃ is 87.2%.
[0101] Comparative Example 6 Compared with Example 1, the difference is that the particle size Dv50 of the first hard carbon material is 7.5 μm, and the particle size Dv50 of the second hard carbon material is 7.5 μm. All other parameters and preparation methods are the same as in Example 1.
[0102] The performance of the sodium-ion battery provided in this comparative example was tested, and the results are as follows: the cell energy density is 122.4Wh / Kg, and the capacity retention rate after 300 cycles at 45℃ is 87.1%.
[0103] Comparative Example 7 Compared with Example 1, the difference is that the particle size Dv50 of the first hard carbon material is 4.0 μm, and the particle size Dv50 of the second hard carbon material is 8.6 μm. All other parameters and preparation methods are the same as in Example 1.
[0104] The performance of the sodium-ion battery provided in this comparative example was tested, and the results are as follows: the cell energy density is 123.6Wh / Kg, and the capacity retention rate after 300 cycles at 45℃ is 85.3%.
[0105] Comparative Example 8 Compared with Example 1, the difference is that R1 of the first hard carbon material is 0.28, and R2 of the second hard carbon material is 0.28. All other parameters and preparation methods are the same as in Example 1.
[0106] The performance of the sodium-ion battery provided in this comparative example was tested, and the results are as follows: the cell energy density is 121.5Wh / Kg, and the capacity retention rate after 300 cycles at 45℃ is 83.8%.
[0107] Comparative Example 9 Compared with Example 1, the difference is that R1 of the first hard carbon material is 0.59, and R2 of the second hard carbon material is 0.59. All other parameters and preparation methods are the same as in Example 1.
[0108] The performance of the sodium-ion battery provided in this comparative example was tested, and the results are as follows: the cell energy density is 118.5Wh / Kg, and the capacity retention rate after 300 cycles at 45℃ is 86.9%.
[0109] Comparative Example 10 Compared with Example 1, the differences are as follows: the R1 of the first hard carbon material is 0.59, and the R2 of the second hard carbon material is 0.28; the particle size Dv50 of the first hard carbon material is 4.1 μm, and the particle size Dv50 of the second hard carbon material is 8.5 μm; the porosity of the bottom layer is 30%, and the porosity of the surface layer is 20%. All other parameters and preparation methods are the same as in Example 1.
[0110] The performance of the sodium-ion battery provided in this comparative example was tested, and the results are as follows: the cell energy density is 114.7Wh / Kg, and the capacity retention rate after 300 cycles at 45℃ is 67.3%.
[0111] The performance testing method is as follows: 45°C Cycle Life Test Method: The sodium-ion batteries prepared in the examples and comparative examples were subjected to cycle tests at 45°C according to the following procedure: Charge at a constant current rate of 1C to 3.8V, and then charge at a constant voltage rate until the current drops to 0.05C; let stand for 5 minutes; discharge at a constant current rate of 1C to 1.5V; let stand for 5 minutes.
[0112] Follow these steps to perform cyclic testing until the sodium-ion battery reaches 300 cycles, at which point the testing will stop.
[0113] 25°C Rate Charging Performance Test: The sodium-ion batteries prepared in the examples and comparative examples were subjected to cycle tests at 25°C according to the following procedure: Charge at a constant current of 0.2C to 3.8V; let stand for 5 minutes; discharge at a constant current of 0.2C to 1.5V; let stand for 5 minutes; repeat the above steps, setting it to (0.2C / 0.5C / 1C / 2C / 3C) and record the discharge capacity of the corresponding rate.
[0114] Table 1 summarizes the information from the examples and comparative examples. The coin cell intercalation curves for the combination of hard carbon and sodium sheets are shown below. Figure 2 As shown, the rate discharge capacity retention rates of Example 1, Comparative Example 1, and Comparative Example 5 are as follows: Figure 3 As shown: Table 1 Summary of information for examples and comparative examples
[0115] Comparing Example 1 and Comparative Example 1, the absence of surface particles reduces electrode porosity and ion transport paths, resulting in a significant decrease in battery energy density.
[0116] Comparing Example 1 and Comparative Example 2, if there are no large particles at the bottom layer, the electrode compaction density decreases, and the energy density of the battery decreases.
[0117] Comparing Example 1 and Comparative Example 4, even though the R2 value of the surface hard carbon is very high, the particle size is large and cannot form an electrode with a gradient distribution of pore structure, resulting in a decrease in rate performance.
[0118] Comparing Example 1 and Comparative Example 5, although the particles of the surface material are very small, the R2 value is low, indicating that the material itself has poor kinetics and does not significantly improve the energy density of the battery cell.
[0119] The above data shows that the present application achieves optimal charge transport dynamics by rationally adjusting the internal microstructure and material properties of the negative electrode along the ion transport direction and charge transport direction to compensate for the polarization effect of the battery reaction, thereby enhancing the internal electrochemical reaction dynamics of the battery and improving the energy density and cycle life of the cell.
[0120] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of this application, and are not intended to limit them. Although this application has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features therein. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of this application.
[0121] Furthermore, those skilled in the art will understand that although some embodiments herein include certain features included in other embodiments but not others, combinations of features from different embodiments are intended to be within the scope of this application and form different embodiments. For example, in the foregoing claims, any of the claimed embodiments can be used in any combination. The information disclosed in this background section is intended only to enhance the understanding of the general background of this application and should not be construed as an admission or in any way implying that such information constitutes prior art known to those skilled in the art.
Claims
1. A composite negative electrode, characterized in that, Includes a current collector and a composite coating disposed on at least one surface of the current collector; The composite coating includes a base layer and a surface layer, wherein the base layer is disposed between the current collector and the surface layer; the base layer comprises a first hard carbon material, and the surface layer comprises a second hard carbon material; Wherein, the ratio R1 of the capacity of the ramp region to the capacity of the plateau region in the charging curve of the first hard carbon material is less than the ratio R2 of the capacity of the ramp region to the capacity of the plateau region in the charging curve of the second hard carbon material.
2. The composite negative electrode sheet according to claim 1, characterized in that, At least one of the following conditions must be met: a. R1 ≤ 0.3; b. The R2 satisfies 0.3 < R2 ≤ 1.
8.
3. The composite negative electrode sheet according to claim 1, characterized in that, At least one of the following conditions must be met: c. The ramp region is the area in the charging curve where the voltage is higher than 0.1V; d. The plateau region is the area in the charging curve where the voltage is below 0.1V.
4. The composite negative electrode sheet according to any one of claims 1-3, characterized in that, At least one of the following conditions must be met: e. The first hard carbon material and the second hard carbon material each independently include one or more of resin carbon, organic polymer carbon, and biomass carbon; f. The particle size of the first hard carbon material is 6-12 μm; g. The particle size of the second hard carbon material is 2-6 μm; h. The porosity of the bottom layer is 15-30%; i. The porosity of the surface layer is 20-55%.
5. A method for preparing the composite negative electrode sheet according to any one of claims 1-4, characterized in that, include: A first slurry is prepared by mixing a first hard carbon material, a first conductive agent, a first binder, and a first solvent. A second slurry is prepared by mixing a second hard carbon material, a second conductive agent, a second binder, and a second solvent. The first slurry and the second slurry are placed on the surface of the current collector to form a composite wet film; after drying, rolling and slitting, the composite negative electrode sheet is obtained.
6. The preparation method according to claim 5, characterized in that, A double-layer coating process is used to coat the first slurry and the second slurry onto the surface of the current collector; The double-layer coating process includes a double-layer single-coating process or a double-layer stepped coating process.
7. The preparation method according to claim 6, characterized in that, The double-layer coating process includes: The first slurry is coated on the surface of the current collector to form a bottom wet film. Before the bottom wet film is completely dry, the second slurry is coated on the bottom wet film to form a surface wet film.
8. The preparation method according to claim 6, characterized in that, At least one of the following conditions must be met: A. The first conductive agent and the second conductive agent each independently include one or more of carbon black, acetylene black, carbon fiber, graphene or carbon nanotubes; B. The first adhesive and the second adhesive each independently comprise one or more of sodium carboxymethyl cellulose, polyacrylic acid, or styrene-butadiene rubber.
9. The preparation method according to any one of claims 6-8, characterized in that, At least one of the following conditions must be met: C. The solid content of the first slurry is 15-50%; D. The solid content of the second slurry is 15-50%.
10. A sodium-ion battery, characterized in that, Includes the composite negative electrode sheet as described in any one of claims 1-4.
